Sikap Anti Korupsi Bagi Calon Legislatif Dalam Rangka Penanggulangan Tindak Pidana Korupsi Di Indonesia Sebagai Wujud Bela Negara (International Forum of Researchers and Lecturers, 2023)
The anti-corruption attitude of legislative candidates in the context of overcoming corruption in Indonesia is an interesting thing to observe and study, Indonesia has stipulated MPR RI Decree Number XI / MPR / 1998 concerning the administration of a State that is Clean and Free of Corruption, Collusion and Nepotism, it turns out that the provisions that have been determined do not become a reference for legislative members so that corruption cases are still rampant within the legislative body. Normative legal research or library research, with a statute approach, conceptual approach, comparative approach, historical approach. The nature of the research used in this research is descriptive-prescriptive, the author uses content analysis. The results of this study are anti-corruption attitudes for legislative candidates with the MPR decree, the Election Law should pay more attention to former corruption convicts who can run as legislative candidates, apart from contradicting the MPR decree, the decision in the Election Law can eliminate public trust in state administrators.